UPAYA PENINGKATAN KUALITAS MINYAK KELAPA KRENGSENGAN DAN BOTOKAN NETRAL MENGGUNAKAN ARANG AKTIF DAN TANAH PEMUCAT - , DAVID IRWAN PRABAWA, Prof. Dr. Ir. Agnes Murdiati, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to determine the effect of the addition of activated carbon: bleaching earth (1:10) on the level of quality krengsengan oil and botokan oil produced. Krengsengan oil and botokan oil treated 20oBe neutralization using NaOH and heated for 10 minutes, then filtered to separate oil soap stock with neutralization. Neutral oil neutralization results in the form of bleaching by using absorbent activated carbon: bleaching earth (1:10) with a variation of the concentration of 0%, 0.5%, 1%, 1.5%, and 2% for krengsengan oil, and 0%, 0.25%, 0.5%, 0.75%, and 1% for botokan oil,each for 15 minutes, then filtered using filter paper so that the resulting oil bleaching. During the process of neutralization and bleaching decline in